(untitled) (SCIENCE TIME JOURNAL, 2026)
The rapid proliferation of artificial intelligence (AI), particularly generative AI, has fundamentally transformed language learning ecologies in higher education. This study examines the mechanisms underpinning the development of discursive competence among students of English philology within AI-mediated environments. Discursive competence is conceptualized as the ability to construct coherent, contextually appropriate, and pragmatically effective discourse across multimodal communicative settings. Employing a qualitative conceptual research design grounded in an integrative review methodology, this study synthesizes recent findings from applied linguistics, AI in education, and computer-assisted language learning (CALL). The analysis draws on a systematic selection of peer-reviewed publications from the period 2021–2026 to identify, classify, and theorize the key mechanisms through which AI technologies mediate discourse development. The results indicate that AI enhances discursive competence through five primary mechanisms: adaptive feedback systems, simulation of authentic discursive interaction, personalization and learner autonomy, multimodal discourse construction, and the development of critical AI literacy. However, the findings also reveal significant emerging risks, including cognitive offloading, reduced discourse originality, ethical concerns related to authorship and algorithmic bias, and inequitable access to AI tools. The study proposes an integrative three-dimensional pedagogical model that combines AI affordances with metacognitive strategies and critical AI literacy to support sustainable discourse development. The paper contributes to the theoretical consolidation of AI-mediated discourse development and offers practical implications for curriculum design, assessment reform, and pedagogical innovation in English philology programs.